2020
DOI: 10.5296/ijld.v10i4.17921
|View full text |Cite
|
Sign up to set email alerts
|

Impeding Factors Towards the Effectiveness of Online Learning During Covid-19 Pandemic among Social Sciences Students

Abstract: During the COVID-19 pandemic, higher learning institutions switched from the traditional face-to-face teaching method to online based teaching. Even though the country is facing crisis due to the pandemic, teaching can still be conducted through online platform. It offers flexibility to both students and academicians. However, online learning is believed to reduce the students’ motivation, performance and lead to mental health problems. To reduce these issues, this study was conducted to determine the impeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…Students may have to bear extra costs aside from their tuition fees or universities will have to charge an online fee to provide stable and reliable internet data for use (Adarkwah, 2021;Piña et al, 2018). In Malaysia, Ramli et al (2020) reports that high data costs hindered learners from fully participating in online learning. Aboagye et al (2020) also reported that with many parents temporarily out of job due to COVID-19 restrictions, students struggled to buy internet data to support elearning.…”
Section: Discussionmentioning
confidence: 99%
“…Students may have to bear extra costs aside from their tuition fees or universities will have to charge an online fee to provide stable and reliable internet data for use (Adarkwah, 2021;Piña et al, 2018). In Malaysia, Ramli et al (2020) reports that high data costs hindered learners from fully participating in online learning. Aboagye et al (2020) also reported that with many parents temporarily out of job due to COVID-19 restrictions, students struggled to buy internet data to support elearning.…”
Section: Discussionmentioning
confidence: 99%
“…Students indicated that they do not receive any support for purchasing data bundles and securing ICT devices for eLearning which makes it difficult for Higher learning Institutions to implement eLearning systems. This is highlighted in a study in Malaysia that showed that the adoption of eLearning systems for Higher Learning Institutions is greatly hindered by high data costs as a result students will not be able to fully participate in online learning [20] . Another study by [21] in private tertiary institutions amidst COVID-19 lockdown in Nigeria showed that implementation of eLearning was slowed down by the expensive eLearning resources such as data and materials.…”
Section: Discussionmentioning
confidence: 99%
“…The students' motivation is derived from the interaction between the educators and their students (Brophy, 2005). According to Ramli et al (2020), conventional education processes deal with physical interaction and communication of the students in classrooms. During this pandemic outbreak, educators face difficulties in motivating students to participate and stay attentive during online learning.…”
Section: Educators and Students' Motivation In Online Learningmentioning
confidence: 99%